Islam and Islamophobia in Post Authoritarian Indonesian Films - Felani, Herman (Unisia, 2024)
Islam and Islamophobia are actual and factual themes in the life of the Indonesian nation. Freedom of expression as a product of the 1998 reform, which was expected to provide opportunities for every citizen, has, in some cases, been misused to spread hatred and lies, which can trigger conflict and social disintegration. Film is a mass communication medium that reflects social reality and society's subconscious, and it can be studied multimodally. Films that raise the issue of Islam in national life and even those that raise the issue of Islamophobia as a global phenomenon after the 11 September 2001 attacks in America are increasingly being produced and enjoyed by audiences around the world. This research attempts to portray the issue of Islam and Islamophobia in Indonesian cinema from historical and social aspects as well as record the narrative of Islam and Islamophobia in Indonesia in the post-reformation era. This research uses a descriptive qualitative content analysis approach with data collection through the literature study method. This research found that commodification and commercialization are not the only reasons for producing Islamic-themed films. This research found that self-identification as a modern, ideal Muslim and adhering to Islamic values is an audience need that is fulfilled by film media as a popular culture product.